Tasks in english in ordinary L1 modules as an inclusive and viable alternative to traditional EMI - Barrios-Espinosa, María Elvira; López-Agudo, Luis Alejandro; Yélamos-Guerra, María Salomé (My University, 2021)
The present paper starts from the premise that, despite the fact that EMI has experienced an exponential growth in the last 15 years (Dearden, 2014; Fenton-Smith et al., 2017; Macaro et al., 2018), there are still a number of compelling arguments that stand against providing all instruction in English in higher education. Among those, insufficient teacher preparation (Drljača Margić & Vodopija-Krstanović, 2018; Kling, 2017) or the fear of negative influence on disciplinary content and discourse learning (Jiménez-Muñoz, 2014) are two of the most frequently mentioned. Bearing these issues in mind, an interdisciplinary group of lecturers from the University of Málaga (Spain) are currently developing an innovation project where a task-based approach is used to deliver content in English in ordinary modules delivered in Spanish (Barrios et al., 2020). The paper presents information about the pedagogical foundations of the intervention and examples of tasks that have been implemented, and the participants’ perceptions about the innovation and their own learning of subject matter content through the medium of English. The paper concludes with some reflections on how this alternative to traditional EMI could contribute towards enhancing university students’ proficiency in academic and professional English while avoiding the understandable reservations that EMI currently faces.
Keywords: Inglés - Estudio y enseñanza; Enseñanza - Innovaciones; Bilingüismo; English medium Instruction (EMI); Higher education; Bilingual programme; Innovation project